Using a Calgary Scale adaptation to detect vasovagal syncope in Colombian university students - Penagos-Guio, Karen Dayanna; Sandoval-Montealegre, Alejandra; Llano-Bautista, Diana Goretty; Galindo-Martínez, José Julián; Reyes-Ortiz, Leonardo José; Tafurt-Cardona, Yaliana (Universidad y Salud, 2021)
Introduction: Vasovagal syncope has an incidence between 10% and 19% in the general population, whose first episodes appear in youth. Objective: To estimate the prevalence of vasovagal syncope in a university student population from the southern Colombia, using a diagnostic questionnaire adapted from the Calgary Scale. Materials and methods: After voluntary signing of the informed consent form, students were surveyed through the Calgary Scale, and a subsequent follow-up questionnaire was conducted on positive participants. Results: 280 students participated in the study and 17% of them obtained a positive score for vasovagal syncope, being positive female participants the largest group. The mean age of participants was 21.45±5.18 years. At the follow-up, 10% of the positive cases had sought out treatment in emergency rooms because of consciousness loss, 4% were hospitalized, and 10% had secondary injuries. Conclusions: Even though an important number of patients was positive on the Calgary Scale, none of them had been diagnosed with neutrally mediated syncope, despite being treated in emergency rooms and/or presenting secondary lesions due to consciousness loss. The use of the Calgary Scale during the assessment of patients being treated for consciousness loss could help to early diagnose vasovagal syncope.